2013
DOI: 10.1210/jc.2013-2193
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Circulating Anti-Müllerian Hormone in Women With Polycystic Ovarian Syndrome Receiving Clomiphene Citrate: A Prospective Observational Study

Abstract: PCOS women with high circulating AMH (≥ 3.4 ng/mL) seem to be resistant to CC and may require a higher starting dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
40
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 13 publications
8
40
1
2
Order By: Relevance
“…Our findings are in agreement with previous article by Mahran A and co-workers [21], who have assessed the impact of serum AMH on the success rate of clomiphene citrate ovulation stimulation in 60 patients with anovulatory PCOS in 187 cycles of therapy, and found serum AMH concentrations to be negatively related to the chances of ovulation. Similarly, Amer SA et al [19], have assessed the effect of serum AMH levels on the outcome of ovarian induction in 20 women with anovulatory PCOS receiving 34 cycles of gonadotrophin regimens.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are in agreement with previous article by Mahran A and co-workers [21], who have assessed the impact of serum AMH on the success rate of clomiphene citrate ovulation stimulation in 60 patients with anovulatory PCOS in 187 cycles of therapy, and found serum AMH concentrations to be negatively related to the chances of ovulation. Similarly, Amer SA et al [19], have assessed the effect of serum AMH levels on the outcome of ovarian induction in 20 women with anovulatory PCOS receiving 34 cycles of gonadotrophin regimens.…”
Section: Resultssupporting
confidence: 93%
“…This cutoff is higher two times than those of previously mentioned by Mahran et al [21], who demonstrated that 3.4 ng/ml was an optimal cut-off among 60 women with PCOS. It is not impossible that different kits for detecting AMH may result in substantial difference in the serum concentration of AMH.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…[3] A modern approach for predicting patient's sensitivity to CC is represented by the AMH measurement. [12] Some authors suggest that an AMH cutoff of 1.2 ng/ ml could be used to predict CC response in obese PCOS women, [13] whereas Maharam et al [12] demonstrated that anovulatory women with AMH greater than 3.4 ng/ ml are resistant to CC and obtain increased ovulation rate with higher starting dose. Furthermore, patients with very high AMH levels may not be suitable for CC treatment and could therefore be directly switched to more effective treatments, such as gonadotrophin ovarian stimulation.…”
Section: Clomiphene Citrate (Cc)mentioning
confidence: 99%
“…Furthermore, patients with very high AMH levels may not be suitable for CC treatment and could therefore be directly switched to more effective treatments, such as gonadotrophin ovarian stimulation. [12] 2.2.2.2. Metformin.…”
Section: Clomiphene Citrate (Cc)mentioning
confidence: 99%